Investigação dos constituintes químicos do chá de Plectranthus ornatus Codd - Matos, Taynara Simão (2019)
Plectranthus ornatus Codd (Lamiaceae), popularly known as “boldo-gambá” and “boldinho”, is a medicinal plant whose leaf or aerial part decoction is used to treat gastrointestinal problems. Despite of its importance in the popular medicinal, there are few chemical and pharmacological reports on the species. Thus, the aim of this study was to investigate the chemical composition of the MeOH soluble fraction from the decoction of the aerial part of P. ornatus, cultivated at the Medicinal Plants Garden Francisco José de Abreu Matos at the Universidade Federal do Ceará –UFC. Successive chromatography procedures, including Sephadex LH-20, C18 cartridge, and HPLC resulted in the isolation of thirteen chemical constituents including two new diterpene derivatives (19-β-D-glucopyranosyl-labda-7,13-diene-15,16-dioicacidand 16-desacetyl-coleon L) and two new flavonoids (3'-β-D-glucuropyranosyl-5,4'-dihydroxy-7-methoxy-flavone and 4'-β-D-glucuropyranosyl-5,3'-dihydroxy-7-methoxy-flavone). It is noteworthy that the flavonoid 4'-β-D-glucuropyranosyl-5-hydroxy-7-methoxy-flavone is already reported in the literature, however the 1H and 13C NMR data of this compound are being presented for the first time. Addicionally, a qualitative comparison of the main isolated compounds from the methanol soluble fraction of P. ornatus with the MeOH fractions from the aerial part decoctions of specimens of three other Plectranthus species (P. barbatus, P. amboinicus, and P. grandis) common in Ceará State was performed. Rosmarinic acid was the main compound in all decoctions. It is worth mentioning the presence of highly hydroxylated and glycosylated compounds. The structural determination of all compounds was performed by interpretation of HRMS and 1H and 13C NMR spectra, and comparison with the literature data. In addition, the biosynthetic route for the isolated diterpenes was suggested. Moreover, the decoctions of the investigated species were assayed for α-glycosidase enzymatic inhibition, and cell viability on human gastric adenocarcinoma cells. None of the studied decoctions showed inhibition of the α-glucosidase enzime. Interestingly, all decoctions showed cell proliferative action and may be indicative for medicinal popular use. However, further tests need to be performed to prove this prophylactic effect against human gastric cells.